2011
DOI: 10.1126/scitranslmed.3001423
|View full text |Cite
|
Sign up to set email alerts
|

CD44-SLC1A2 Gene Fusions in Gastric Cancer

Abstract: Fusion genes are chimeric genes formed in cancers through genomic aberrations such as translocations, amplifications, and rearrangements. To identify fusion genes in gastric cancer, we analyzed regions of chromosomal imbalance in a cohort of 106 primary gastric cancers and 27 cell lines derived from gastric cancers. Multiple samples exhibited genomic breakpoints in the 5' region of SLC1A2/EAAT2, a gene encoding a glutamate transporter. Analysis of a breakpoint-positive SNU16 cell line revealed expression of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 43 publications
1
57
0
Order By: Relevance
“…Previous molecular studies of GC have primarily focused on characterizing aberrations at the DNA level such as mutations, copy number amplifications, and fusion genes [3][4][5][6][7][8][9][10] . Alternatively, while GC gene expression studies using microarrays and RNA-sequencing have been reported, no study to date has reported a systematic analysis of RNA-edited sequence variation in primary GCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous molecular studies of GC have primarily focused on characterizing aberrations at the DNA level such as mutations, copy number amplifications, and fusion genes [3][4][5][6][7][8][9][10] . Alternatively, while GC gene expression studies using microarrays and RNA-sequencing have been reported, no study to date has reported a systematic analysis of RNA-edited sequence variation in primary GCs.…”
Section: Discussionmentioning
confidence: 99%
“…A heterogeneous disease arising from the complex interplay of host factors and environmental risk agents such as Helicobacter pylori, GCs have been shown to exhibit a wide spectrum of molecular aberrations 3 . At the DNA level, we and others have shown that GCs can exhibit distinct patterns of chromosomal amplifications and deletions involving oncogenes and tumor suppressor genes (ERRB2, FGFR2, and RB1), gene fusions (eg CD44-SLC1A2, CLDN18-ARHGAP26), microsatellite instability, and somatic mutations in genes such as TP53, ARID1A, and RhoA [3][4][5][6][7][8][9][10] . Clinically however, few of these molecular alterations have significantly impacted the treatment of GC patients to date, with the exceptions of traztuzumab treatment in ERBB2-positive GC, and ramucirumab (an anti-angiogenic therapy) in advanced GC 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…80 The second fusion gene identified in GC was CD44-SLC1A2, which juxtaposes the SLC1A2 glutamate transporter against the CD44 promoter. 81 …”
Section: Tmprrs2-erg In Prostate Cancermentioning
confidence: 97%
“…We focused on detecting fusion genes since not only hematologic but also solid cancers are known to be driven by fusion genes resulting from pathogenic chromosomal translocation or inversion (Tomlins et al 2005;Wong et al 2009;Tao et al 2011;Welch et al 2011). Our approaches identified 52 fusion genes ( Fig.…”
Section: Fusion Gene Analysismentioning
confidence: 99%